2018
DOI: 10.1371/journal.pone.0197180
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative carotid artery centerline extraction in MRI

Abstract: Centerline extraction of the carotid artery in MRI is important to analyze the artery geometry and to provide input for further processing such as registration and segmentation. The centerline of the artery bifurcation is often extracted by means of two independent minimum cost paths ranging from the common to the internal and the external carotid artery. Often the cost is not well defined at the artery bifurcation, leading to centerline errors. To solve this problem, we developed a method to cooperatively ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…In the last decades, several research groups reported on various methods to enable automated plaque characterization on multi-contrast MRI by segmenting plaque components. Computer vision approaches such as shape fitting, active contours, and level sets, in combination with simple machine learning methods such as classification and clustering, were attempted early on [9,15,16,17,18,19,20,8,21,10,11,12,13,14]. In more recent years, convolutional neural networks (CNN), including U-Net, have gained increasing attention [22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades, several research groups reported on various methods to enable automated plaque characterization on multi-contrast MRI by segmenting plaque components. Computer vision approaches such as shape fitting, active contours, and level sets, in combination with simple machine learning methods such as classification and clustering, were attempted early on [9,15,16,17,18,19,20,8,21,10,11,12,13,14]. In more recent years, convolutional neural networks (CNN), including U-Net, have gained increasing attention [22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes even additional delineation of a muscle region is needed for intensity re-scaling [9,15,16]. While there are some studies where the CA was located using the lumen seed points in the distal slices alone, or in different CA branches [18,11,19,12,13], user interaction is still necessary, and no studies show robustness to seed positioning. A couple of publications report on automated CA localization, but the detection area is limited to manually selected slices [10].…”
Section: Introductionmentioning
confidence: 99%